Optimal sizing of off-grid hydrokinetic-based hybrid renewable power systems for a house load demand - Gokcek, Murat; Kale, Cihangir (Wiley, 2021)
The usage of stand-alone power systems represents an excellent choice for remote communities that are impossible to couple to the electricity distribution network practicably. The current research aims to design a no grid tied hybrid system on the basis of a PV-wind turbine-hydrokinetic turbine and diesel generator, for the purpose of meeting the electricity needs of a house near the Seyhan River, Turkey. A software that performs hybrid optimization of systems that can generate energy using different energy sources was utilized for modeling the operation of systems and identifying the appropriate architecture. In the current research, simulations were carried out for eight different (off-grid) power systems. The best optimized off-grid hybrid power system comprises a photovoltaic array of 7.87 kW, two wind turbines, one hydrokinetic turbine, a diesel generator of 7 kW, lead-acid batteries of 49 kWh, and a converter of 4.95 kW. The results of the present research demonstrated that the total net present cost was $161 327.08, while the levelized cost of electricity was $0.609/kWh for the optimized system. Furthermore, the renewable usage fraction and carbon dioxide emissions are 26.4% and 838.63 kg/year, respectively. In accordance with the simulation findings, the wind-hydrokinetic power system has higher levelized cost of electricity and total net present cost in comparison with other power generation systems.
Keywords: hydrokinetic turbine; levelized cost; off? grid power system; renewable energy